Potensi Pelanggaran Hak Asasi Manusia Melalui Eksistensi Aplikasi Identifikasi Nomor terhadap Wirausaha - Steven Nigel Bunalven; Maureen Cornellia David (Fakultas Hukum Universitas Tarumanagara, 2022)
The Indonesian constitution as a feature of the rule of law takes the supremacy of human rights in it.Personal self-protection, honor, and dignity as an essential part of human rights must consequently beupheld and should not be neglected for any reason and in any form. Refuse to be an exactism, certainexceptions to human rights are strictly permitted (limitative) and must be based on legal rules (juridical).The tagging system in the number identification application actually injures personal protection, honor,and dignity for all elements of society, especially entrepreneurs. In the midst of the spirit of nationaleconomic recovery after the Covid-19 pandemic, Entrepreneurs who are the central actors are threatenedin implementing their entrepreneurship due to the threat of reputation that can be easily injured by thetagging system. This then needs to be a concern of the Government because the tagging system that existsin this number identification application not only threatens the business climate and national economicrecovery after the Covid-19 Pandemic, but also threatens the supremacy of personal protection, honor anddignity as human rights that must be protected. adopted by the constitution.